2011
DOI: 10.1039/c1cp00015b
|View full text |Cite
|
Sign up to set email alerts
|

Photon induced isomerization in the first excited state of the 7-azaindole–(H2O)3 cluster

Abstract: A picosecond pump and probe experiment has been applied to study the excited state dynamics of 7-azaindole-water 1 ∶ 2 and 1 ∶ 3 clusters [7AI(H(2)O)(2,3)] in the gas phase. The vibrational-mode selective Excited-State-Triple-Proton Transfer (ESTPT) in 7AI(H(2)O)(2) proposed from the frequency-resolved study has been confirmed by picosecond decays. The decay times for the vibronic states involving the ESTPT promoting mode σ(1) (850-1000 ps) are much shorter than those for the other vibronic states (2100-4600 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
56
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(65 citation statements)
references
References 23 publications
(44 reference statements)
9
56
0
Order By: Relevance
“…Vibrational mode selective tautomerization dynamics was experimentally observed from frequency-resolved, 34,37,38 and picosecond pump and probe experiments. 35 Excited state ab initio calculations suggest that the vibrational mode selective tautomerization mechanism in all the above mentioned complexes is due to a concerted double or triple proton transfer, while the electron remains in the π * orbital of the chromophore. Thus, the 7AI molecule be-comes a special case in which the ESHAT is unlikely to take place in the excited state when both functional groups are connected by intermolecular H-bonds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vibrational mode selective tautomerization dynamics was experimentally observed from frequency-resolved, 34,37,38 and picosecond pump and probe experiments. 35 Excited state ab initio calculations suggest that the vibrational mode selective tautomerization mechanism in all the above mentioned complexes is due to a concerted double or triple proton transfer, while the electron remains in the π * orbital of the chromophore. Thus, the 7AI molecule be-comes a special case in which the ESHAT is unlikely to take place in the excited state when both functional groups are connected by intermolecular H-bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Upon electronic excitation, the basicity of the nitrogen atom in the six member ring increases together with the acidity of the nitrogen atom in the five member ring. In the gas phase, it has been shown that when both nitrogen atoms are connected by a H-bonded molecular wire of two H 2 O, 34,35 CH 3 OH, 36, 37 CH 3 CH 2 OH 38 molecules or in the case of the Hbonded (7AI) 2 dimer 39 and other substituted 7AI dimers, 40 the increased basicity and acidity of the two sites trigger the excited state tautomerization of 7AI. Vibrational mode selective tautomerization dynamics was experimentally observed from frequency-resolved, 34,37,38 and picosecond pump and probe experiments.…”
Section: Introductionmentioning
confidence: 99%
“…A well-known example is 7-azaindole (7AI, Figure 1), which forms doubly hydrogen bonded dimers in solution [2], while the X-ray data reveal a tetrameric structure in the crystalline state [3]. Different stoichiometries and structures are possible for the complexes of 7AI with methanol and water: 1 : 1, 1 : 2, and 1 : 3 species have been detected [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In a similar system, 7-azaindole with solvent molecules, CC2 calculations seem to show that the solvent-induced transfer should be a sequential proton transfer in the case of 7-azaindole-(NH 3 ) 2 41 and a concerted multiple proton transfer in the case of 7-azaindole-(methanol) 2 42-44 and 7-azaindole-(H 2 O) 2,3 clusters. [45][46][47] …”
Section: Discussionmentioning
confidence: 98%